Ответы и объяснения

2013-09-08T13:41:12+04:00
Х^3-49x=0  
 x(x^2-49)=0  
x(x-7)(x+7)=0  
 X=0  
X-7=0  
x=7


2013-09-08T13:49:50+04:00
10) x^3 + 2x^2 - 9x - 18 = 0;
      x^2(x + 2) - 9 ( x + 2) = 0;
      (x+2)(x^2 - 9) = 0
     1. x+2 =0     2. x^2 - 9 =0
         x= -2;           x^2 = 9;
                             x= + - 3;

6) x^2 + 8x +16 - x^2 = 2x + 1;
    8x - 2x = 1 - 16;
    6x = -15;
    x = - 15 / 6;
    x = - 2,5 ;

9) x^2( x - 3) + 2 (x -3) = 0;
    (x - 3)(x^2 + 2) = 0
    x - 3 = 0         x^2 + 2 =0
    x = 3              x^2= -2 - нет решений
   

11) 7 - ( 8x^2 -6x - 2) = 10x - 8x^2;
     7 - 8x^2 + 6x + 2 = 10x - 8x^2;
     10x - 6x = 9 ;
     4x = 9;
      x = 9/4;
      х = 2,25.

12) 25 - 10x + x^2 - ( 6x^2 - x - 2) = 2x - 5x^2;
     25 - 10x + x^2 - 6x^2 +x + 2 = 2x - 5x^2 ;
     11x = 27;
     x = 27/11;
     x= 2 целых и 5/11;
     Ответ: 6) - 2,5 ; 9) 3 ; 10) - 3 ; -2 ; 3 ;  11) 2,25; 12) 2 целых и 5/11.
Упс, в 11) 7- (8x^2 - 6x - 2) = 10x - 8x^2 ===> 7 - 8x^2 + 6x +2 = 10x - 8x^2 ===> 4x = 9===> x = 9/4; ==> x = 2 , 25